An analysis of the asset-based community development approach to early childhood development interventions in Grahamstown township pre-schools: a case study of the Centre for Social Development and Rhodes University Community Engagement - Maponya, Mapula (Rhodes University, Faculty of Humanities, Department of Sociology, 2018)
Is the glass half-full or half-empty? The purpose of this research was to show how Centre for Social Development and Rhodes University Community Engagement applies the Asset-Based Community Development approach in ECD interventions in Grahamstown township pre-schools. The subsidiary goals of the research were to highlight the challenges in the Early Childhood Development sector in Gahamstown, find out how the approach contributes to empowerment, participation and sustainability, and analyse the challenges that CSD and RUCE face in applying the approach and the relationship between the two organisations. The case study focused on the Centre for Social Development (CSD) and Rhodes University Community Engagement (RUCE). These two cases established projects that aim to improve Grahamstown township pre-schools. The apartheid system created a childhood of adversity for black children including inadequate access to social services, quality nutrition, health care and education. Black children in rural areas and townships faced tremendous obstacles in terms of access to quality ECD centres due to poverty and lack of adequate resources. In Grahamstown, various problems such as unemployment, poverty and restrictive apartheid regulations created a need for ECD interventions. Both organisations applied the Asset-Based Community Development approach to improve ECD in Grahamstown. The asset-based approach was created as a response to the impact of the needs-based approach. The needs- based approach focuses on deficiencies that exist in a community and uses outside experts and resources to address the deficiencies. The needs-based approach builds communities from the outside in, further disempowers community members and creates an environment of dependency. The asset-based approach on the other hand, was created to change the legacy of dependency by focusing on capacity building. A capacity-focused paradigm recognizes the gifts, skills and talents of community members. This approach is bottom- up beginning with what is available in the community and building on that. The approach aims to empower people, create a positive outlook on circumstances, and encourages organisations to work together with community members in community development projects. To achieve the main and subsidiary goals of the research, qualitative research was conducted using the case study method. In pursuing the objective of the thesis, I conducted research among ECD practitioners, student volunteers and staff from CSD and RUCE. Based on the findings it is clear that the application of the Asset-Based approach has a positive impact on ECD practitioners, children at the pre-schools and student volunteers. Through the application of the ABCD approach, ECD practitioners became proactive and took the driving seat in the development process. The ECD practitioners built strong relationships with community members and outside organisations. They have improved their skills and qualifications, and are on their way to restoring their agency, finding their voice and achieving independence. This has a positive impact on children at the pre-schools as they receive quality education and care. There are various challenges and contradictions in the application of the approach but the ECD practitioners view the communities in which they operate as half-full and not half-empty
Keywords: Uncatalogued